The Principality of Moldavia in the foreign policy of Poland from the victory at Vienna to the Treaty of Karlowitz (1683–1699) - Baidaus, Eduard (Balcanica Posnaniensia. Acta et studia, 2003)
The aim of this article is to analyse Moldavia's role in John III Sobieski's efforts to rebuild the Polish-Lithuanian Commonwealth's influence in South-Eastern Europe in the years 1683–1699. The author presents both the military campaigns and diplomatic efforts undertaken by Poland towards the principality, drawing attention to the rivalry with the Habsburg Empire and the complex political game played by the local Moldavian elites. The source material consists of diplomatic reports, Moldavian chronicles, political correspondence and documents from Polish and Romanian archives. The analysis uses a historical-comparative method and critical analysis of sources. As the text shows, despite several military successes (including the capture of Jassy in 1686), the actions of the Polish-Lithuanian Commonwealth did not bring about a lasting change in the status of Moldavia, mainly due to the conflicting interests of the allies of the Holy League and the unstable attitude of the hospodars, especially Constantine Cantemir. The Treaty of Karlowitz in 1699 brought Poland the recovery of Podolia and the right bank of Ukraine, but also forced it to renounce its claims to Moldavia.